EXAMINING OF CURRICULUM OF RELIGIOUS CULTURE AND MORAL KNOWLEDGE CLASSES IN PRIMARY SCHOOLS IN TURKEY FROM APPROACH OF DEVELOPMENT OF EDUCATIONAL PROGRAM - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2014)
Curriculums as main component of educational system in Turkey have been changed from time to time depending on developments in the field of education in the World. Curriculum of religious culture and moral knowledge classes in primary schools is one of the important area that changed in 2004 and put in the practice in educational year of 2005-2006, and then renewed in 2010. The new curriculum is designed according to Constructivism considering student centrism, multiple intelligence theory and individual differences. From that time, there are researches on the curriculum to evaluate success of the program from different aspects such as its instruction methods, techniques, subjects, application etc. Considering different researches on the curriculum, we intended to find out opinions of teachers of religious culture and moral knowledge classes in primary schools about effectiveness of the changes on the curriculum as applicators and we interviewed fifty teachers from different schools in Istanbul. Our research aims to evaluate effectiveness of the changes on the curriculum according to opinions of teachers in four aspects of development process of educational program: Aims of program, subjects, instruction methods, and application. We want to share results of our research comparing with old version of the curriculum and discuss them with making recommendation for possible changes in the future and hopefully it will be beneficial.
Keywords: Education; Religious Education; Curriculum; Development of Educational Program